The Effect of Benson Relaxation Technique on a Scale of Postoperative Pain in Patients with Benign Prostate hyperplasia at RSUD dr. H Soewondo Kendal - Arifianto Arifianto; Dwi Nur Aini; Novita Diana Wulan Sari (Universitas Muhammadiyah Semarang, 2019)
Background : Benign Prostate Hyperplasia (BPH) is a disease enlargement or hypertrophy of the prostate. Each surgery will arise as a result of wound incision procedures. Based on pre-study post operative patients with benign prostate hyperplasia in Dr.H Soeowndo Kendal General Hospital 4 out of 5 patients said that after surgery they experienced pain around the post operative .These wounds will stimulate the pain response Handling of non-pharmacological that can be done is by Benson relaxation therapy. The objective of this research there is an effect of Benson relaxation technique on a scale of postoperative pain in patients with Benign Prostate Hyperplasia at RSUD dr. H Soewondo Kendal. Methods : Design Research use quasi experiment. designs with pre and post-test without a control sample with 32 people. Relaxation Benson techniques are done taxable income provision with analgesic duration of 8 hours. And after before given relaxation techniques Benson carried measurement scale with a numeric pain rating scale. Result : Results of Statistics Wilcoxon Sign Rank test with confidence level of 95% (α = 0.05) and obtained p value 0.000 < 0.05. Conclusion : the result of this research there is an effect of benson relaxation technique on a scale of postoperative pain in patients with Benign Prostat Hyperplasia at RSUD dr. H Soewondo Kendal.